(untitled) (Vietnam Journal of Community Medicine, 2022)
Histopathological classification of thymic tumors 2015, WHO update 2021, thymic carcinomas are divided into 3 large groups: Thymoma/benign thymic tumors; Thymic carcinoma/ Thymus cancer; Thymic neuroendocrine/ Neuroendocrine thymoma. Thymic carcinoma (Thymic Carcinoma - TC) accounts for 70% of cases of Thymoma; In which, the type of squamous carcinoma (Thymic Squamous Cell Carcinoma -TSCC) is very rare, diagnosed based on histopathology criteria and immunohistochemistry. Patients with TSCC also often have clinical symptoms associated with mediastinal tumor: Invasion of intramediastinal structures is common, including superior vena cava syndrome; However, the common paraneoplastic syndromes in thymoma such as myasthenia gravis, erythrocytosis, and hypogammaglobulinemia are very rare in TSCC. TSCC has a very high malignancy and is often metastasized. The detection rate of distant metastases is up to 50-65% at the time of diagnosis. Common sites of metastasis include lung, liver, brain, and bone. The prognosis for TSCC is very poor with a 5-year survival rate of 30%. The mean age at diagnosis was 50. We introduce a 70-year-old male patient, who came to the National Lung Hospital for examination and treatment, was diagnosed with TSCC by histopathology and immunohistochemistry with a diagnostic approach to help colleagues industry for reference.